Challenges in implementing the Electronic Government Procurement (e-GP) in Public Works Department (PWD) - Mahmud, Tasnuva (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.